Occurrence of multidrug-resistant tuberculous meningitis associated with injury during spinal surgery: A case report - Mingwei Zhao; Ling Liu; Miao Wang; Weidong Zhou; Minglei Zhang; Han Xiao; Yu Pang (Journal of Infection and Public Health, 2020)
Here we describe a case of multidrug-resistant tuberculous meningitis associated with injury inflicted during spinal surgery. A 54-year-old man was diagnosed with multidrug-resistant spinal tuberculosis (TB). Anterior debridement and fusion with posterior fusion and instrumentation were conducted to remove damaged bone and TB-associated granulomatous tissue. After surgical decompression, a lancet wound (about 5 mm in length) was discovered in the cerebral dura mater at the L3 position of the vertebral body. At four weeks post-surgery, the patient experienced fever, hemiparesis, and aphasia. Cerebrospinal fluid (CSF) findings were consistent with TB meningitis, while in vitro susceptibility test results confirmed that the patient had multidrug-resistant TB. Our data highlight a possible TBM infection associated with a surgical lesion in a spinal TB patient. Rapid molecular diagnostics are urgently needed to formulate efficacious regimens for treating these patients.